The Role of Corporate Governance in Improving the Quality of Integrated Reporting: A Systematic Literature Review - Gita Deprianti; Yusnaini Yusnaini (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the role of corporate governance in improving the quality of integrated reporting through a Systematic Literature Review (SLR) approach. Integrated reporting has developed as a comprehensive reporting model that combines financial and non-financial information to explain how organizations create value in the short, medium, and long term. However, the quality of integrated reporting remains varied across companies, indicating that internal governance mechanisms play an important role in determining disclosure quality. This study applies the PRISMA framework to systematically identify, screen, and evaluate relevant literature from Scopus, SINTA, and Garuda databases using keywords related to corporate governance, integrated reporting, board characteristics, audit committee, and governance mechanisms. From an initial 81 articles, 28 articles met the inclusion criteria and were analyzed further. The findings show that corporate governance significantly contributes to integrated reporting quality through stronger monitoring, accountability, and transparency in corporate disclosure practices. The most dominant governance variables identified in the literature are board size, board independence, audit committee, and ownership structure. Among these variables, audit committee activity and board independence consistently show positive effects because they strengthen internal monitoring and improve the credibility of disclosed information. Nevertheless, several studies indicate inconsistent results, suggesting that governance effectiveness is highly influenced by institutional context, regulatory environment, and company characteristics. This study recommends future research to explore contemporary governance variables and broader cross-country comparative analysis.